A cross-sectional study on achievement of performances of Kayakalp program parameters between a Medical College and District Hospital of West Bengal - Tanusri Ray; Eashin Gazi; Tushar Kanti Saha; Kaushik Ishore (MRIMS Journal of Health Sciences)
Background “Kayakalp” is a National initiative to give awards to those public health facilities that demonstrate high level of cleanliness, hygiene, and infection control. It encourages every public health facility in the country to work toward standards of excellence to help the facilities to maintain cleanliness and hygiene. Objective The objective of the study was to find out baseline data, assess different key areas, and to compare the performance of different parameters mentioned in the Kayakalp program. Materials and Methods An observational cross-sectional study was conducted in two hospitals (one medical college and one district hospital) of West Bengal during 2020–2021. The study population consisted of staffs and admitted patients. Direct observation, record review, staff interview, and patient interview were done using the Kayakalp assessment checklist, relevant hospital records, etc. Assessment of performance was based on seven key parameter-hospital upkeep, sanitation and hygiene, hospital support service, waste management, infection control, hygiene promotion, and feedback mechanism. Collected data were entered in Microsoft Office Excel data sheet and analyzed there. The presentation of data was done using the principles of descriptive statistics in tabular form and bar diagrams. Results The studied district hospital scored much higher (total score 371) than the medical college (total score 237) in almost all key areas. Different component-wise following scores were noted among those two hospitals: hospital upkeep (55.4% vs. 37.7%), sanitation and hygiene (59.3% vs. 26%), hospital support service (57.5% vs. 47.5%), waste management (60% vs. 43.3%), infection control measures (61% vs. 59%), and hygiene promotion (51.3% vs. 35%). There was no system for feedback mechanism from the public on cleanliness in the studied medical college care hospital. Conclusion All health institutions should be under the Kayakalp program for improvement in the quality of patient care-related services.